A REVIEW ON SCREENING METHODS OF BREAST CANCER, CANCER BIOMARKERS AND PHYTOCONSTITUENTS AGAINST BREAST CANCER - V, Jayashree; S, Priyanka; A, Reshma (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â A cancer biomarker refers to a substance or process that is used as an indicative the presence of cancer in the body. A biomarker may be a molecule secreted by a tumor or a specific response of the body to the presence of cancer. Biomarkers are utilized in three elementary ways as a diagnostic tool, prognostic tool, and predictive tool. The screening tests employed are clinical and breast exams, mammography, hereditary screening, ultrasound, and attractive reverberation imaging. Biomarkers involved in breast cancer are human epidermal growth factor-2, estrogen receptor, progesterone receptor, Cyclin D1, and Cyclin E. Specific bioactive phytoconstituents used as anticancer include curcumin, genistein, resveratrol, isothiocyanates, silymarin, diallyl sulfisoxazole, lycopene, apigenin, and gingerol. Hence, this review indicates the study of screening methods, various biomarkers in breast cancer and phytoconstituents against breast cancer.